UTILIZATION OF INFORMATION SERVICES TO IMPROVE ACHIEVEMENT MOTIVATION STUDENTS OF MTs STATE BANYUWANGI - Rizal Ahsan Saifur (SOSIOEDUKASI, 2020)
This research was conducted at MTs. Negeri Banyuwangi in the 2017/2018 school year where motivation for achievement is still low. The purpose of writing this guidance counseling action research is to find out whether information services can increase student achievement motivation. Data collection methods are questionnaires and observations. The data analysis method is descriptive. The results obtained from this study are information services can increase student achievement motivation in following the teaching and learning process. From the results of descriptive data analysis also showed an increase in students' understanding of the importance of having achievement motivation so that their motivation can be increased, ranging from 26.56% to 43.69% with a high category. The conclusion obtained from this study is that information services can increase student achievement motivation in following the teaching and learning process.